A multi-channel strategy involving street trade and supermarket/hypermarket trade in West African countries - (:unkn) unknown (My University, 2020)
In this paper, we examine a specific multi-channel strategy by exploring the following research question: “How can street trade (traditional in West Africa) and mass distribution (more recent) complement each other and also have an impact?”, through the case study of Fan Milk, a dairy-product retailer. The analysis of a series of 23 interviews with customers leads to the formulation of contributions to the literature and the practice.
Keywords: African Research